“The piano that no longer plays”—The impact ofintersecting traumas on narrative identity in HertaMüller's novel Atemschaukel - Merivuori, Liisa (Wiley, 2025)
In this article, I analyze the intersecting traumas that appear in Herta Müller's novel Atemschaukel (2008), and their effect on the main character's narrative identity, through the perspective of feminist trauma studies and narrative hermeneutics. I argue that Atemschaukel describes three intersecting traumas: hunger in the Gulag, extreme minority stress, and lifelong homesickness. Those traumas have several effects on the narrative identity of the main character: isolation from the world, lack of belief in a better future, and inability to see possibilities for change. The combination of feminist trauma studies and narrative hermeneutics will generate new understanding of the effects of intersecting traumas and the ethical potential of traumatic narratives.